A fish kill at the Aposelemis dam (Crete, Greece) caused by heavy parasitism by Ichthyobodo sp - Katharios, Pantelis (Journal of fish diseases, 2023)
© 2022 The Authors. Journal of Fish Diseases published by John Wiley & Sons Ltd.